2018
DOI: 10.1038/nmeth.4631
|View full text |Cite
|
Sign up to set email alerts
|

Improved Ribo-seq enables identification of cryptic translation events

Abstract: Ribosome profiling has predicted thousands of short open reading frames (sORFs) in eukaryotic cells, but still suffers from substantial levels of noise. PRICE (https://github.com/erhard-lab/price) is a computational method modeling the experimental noise to accurately resolve overlapping sORFs and non-canonical translation initiation. We experimentally validated translation using MHC-I peptidomics and saw that sORF-derived peptides efficiently enter the MHC-I presentation pathway and thus constitute a substant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
163
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 158 publications
(183 citation statements)
references
References 23 publications
(30 reference statements)
3
163
0
Order By: Relevance
“…Of these, 192 were from smORFs identified in at least two Ribo-Seq experiments (Supplementary Data 3), and 41 lacked an in-frame AUG start codon. A previous study was also able to detect over 100 microprotein peptides in the same proteomics dataset, which is consistent with and expanded by these data 65 . Representative spectra of peptides from smORF-encoded microproteins demonstrate good fragment ion coverage, regardless of the number of times detected and cell lines found in by Ribo-Seq (Fig.…”
Section: Resultssupporting
confidence: 89%
“…Of these, 192 were from smORFs identified in at least two Ribo-Seq experiments (Supplementary Data 3), and 41 lacked an in-frame AUG start codon. A previous study was also able to detect over 100 microprotein peptides in the same proteomics dataset, which is consistent with and expanded by these data 65 . Representative spectra of peptides from smORF-encoded microproteins demonstrate good fragment ion coverage, regardless of the number of times detected and cell lines found in by Ribo-Seq (Fig.…”
Section: Resultssupporting
confidence: 89%
“…The HSV-1 genome is about 152kb in size and known to encode at least 80 open reading frames (ORFs), many of which have been extensively studied. Large-scale RNA-seq and ribosome profiling recently revealed that the coding capacity of three other herpesviruses, namely human cytomegalovirus (HCMV), Kaposi's sarcoma-associated herpesvirus (KSHV) and Epstein-Barr Virus (EBV) is significantly larger than previously thought [2][3][4][5] . For HCMV and KSHV, in particular, hundreds of new viral gene products were identified.…”
Section: Mainmentioning
confidence: 98%
“…Often, MS-based immunopeptidomic discoveries are limited to the standard, available protein sequence database, usually containing only annotated protein-coding sequences. Recently, several studies have included protein sequences derived from the translation of transcripts identified from RNA-Seq, or from ribosome profiling, into MS-based searches 9,[23][24][25][26][27][28] . Overall, these studies warrant further development in many key aspects: Importantly, elevated false discovery rates (FDRs) for the non-canonical space can occur when MS reference data are populated with protein sequences derived from all potential three-or six-frame translations of transcribed regions 29 .…”
Section: Introductionmentioning
confidence: 99%